2022
DOI: 10.3390/sym14040796
|View full text |Cite
|
Sign up to set email alerts
|

Sandstone Modeling under Axial Compression and Axisymmetric Lateral Pressure

Abstract: The problems of the mechanical state of rocks and other brittle materials are studied from different sides in a large number of publications, the flow of which does not weaken with time, which is explained by the relevance and complexity of these problems. Quantitative values of strength and other characteristics of such materials can be obtained experimentally or using numerical and analytical models. This work is aimed at developing an analytical model for analyzing the state of brittle material on the examp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The expediency of continuing research is indicated by a certain analogy of stress-strain curves (Figures 1-3) for concrete [25,26], rock materials [21,22], geopolymers [27][28][29][30], frozen soils, and other brittle materials [31][32][33][34]. The focus of future research on the topic may be on the right branch of the full stress-strain (or load-displacement) curve.…”
Section: Discussionmentioning
confidence: 99%
“…The expediency of continuing research is indicated by a certain analogy of stress-strain curves (Figures 1-3) for concrete [25,26], rock materials [21,22], geopolymers [27][28][29][30], frozen soils, and other brittle materials [31][32][33][34]. The focus of future research on the topic may be on the right branch of the full stress-strain (or load-displacement) curve.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the process of destruction of solids is ordered and that "the hierarchy of the scale of destruction begins with the size of the crystal lattice and continues up to the size of tectonic plates in geospheres" [18]. Taking these circumstances into account, an array (or sample) of brittle material can be considered as a structure with a mechanical state and properties that depend on the impacts exerted upon it [19][20][21]. Such a structure (construction) can be considered as a macro-object consisting of mesoscale elements with mechanical states and interactions with each that other determine the strength and stiffness of the degrading brittle material.…”
Section: Methodology 21 Degrading Materials As a Macro-object Consist...mentioning
confidence: 99%